Kavisha Mazzella interviewed by Salvatore Rossano in the Salvatore Rossano folklore collection. - Mazzella, Kavisha, 1959-; Rossano, Salvatore, 1975- (2019)
Folkloric recording.
Accompanying material includes poetry and songs: Madona del mare, Vola rondine vola, Wedding sheets, Fearles note, Sing for no-one, sing for everyone.
Recorded on 17 January 2019 in Northcote, Melbourne, Victoria and 22 January 2019 at Muckleford State Forest, Muckleford, Victoria.
Digital master available
Timed summary available.
Keywords: Mazzella, Kavisha, -- 1959- -- Interviews; Italian Australians -- Interviews; Musicians -- Australia -- Interviews